Erythema Multiforme Following Smallpox Vaccination. Issue 1 (1st January 2014) - Storie, Erin B.; Perry, Adam
ABSTRACT: Erythema multiforme (EM) is an acute self-limited eruption with multiple possible precipitators including drugs, infections, and in a small percentage, vaccinations. The lesions of EM can vary in presentation and are frequently misdiagnosed. With the reinstitution of the smallpox vaccination program for deploying service members, there is an increased need for military providers to be aware of the adverse reactions to be expected with this vaccination. We present the case of a 19-year-old active duty male who developed EM 14 days after receiving vaccination for smallpox.